2015
DOI: 10.1038/srep14233
|View full text |Cite
|
Sign up to set email alerts
|

Regional microbial signatures positively correlate with differential wine phenotypes: evidence for a microbial aspect to terroir

Abstract: Many crops display differential geographic phenotypes and sensorial signatures, encapsulated by the concept of terroir. The drivers behind these differences remain elusive, and the potential contribution of microbes has been ignored until recently. Significant genetic differentiation between microbial communities and populations from different geographic locations has been demonstrated, but crucially it has not been shown whether this correlates with differential agricultural phenotypes or not. Using wine as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
185
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(235 citation statements)
references
References 50 publications
(77 reference statements)
19
185
0
6
Order By: Relevance
“…In agreement with previous studies suggesting that microorganisms of the vineyard (7) and wine yeasts (12) are components of the terroir, we can assume that O. oeni is also part of the terroir because each region holds a different combination of strains and a majority of unique strains. However, the strains are not genetically specific to the regions and a nonnegligible fraction of them is present in diverse regions.…”
Section: Discussionsupporting
confidence: 73%
“…In agreement with previous studies suggesting that microorganisms of the vineyard (7) and wine yeasts (12) are components of the terroir, we can assume that O. oeni is also part of the terroir because each region holds a different combination of strains and a majority of unique strains. However, the strains are not genetically specific to the regions and a nonnegligible fraction of them is present in diverse regions.…”
Section: Discussionsupporting
confidence: 73%
“…These authors even predicted the metabolome of the wine from the microbial composition by using machine learnig techniques [54]. Similar results have also been generated from other studies [55,56].…”
Section: Analysis Of Alcoholic Fermentationsupporting
confidence: 71%
“…The microbial aspect of terroir was recently illustrated by different studies that suggested a link between vineyard environmental conditions and microbial inhabitation patterns and revealed the importance of microbial populations for the regional identity of wine (30,31).…”
mentioning
confidence: 99%